Appropiate actions for integral development during early childhood. A parents’ guide - Martínez, Mayluc (2017)
In the present article, we present a number of recommendations that parents must take into account with regard to the integral development of their children, particularly during the first three years of their life; in relation to the alarm signals  that may appear and that are linked to some disorder, as well as behaviors in excess or deficits, which suggest actions (incentives and reinforcements) that parents can undertake in relation to motor development, imitation, communication, autonomy, social interaction and games.